2019
DOI: 10.1002/smll.201904912
|View full text |Cite
|
Sign up to set email alerts
|

2D In2S3 Nanoflake Coupled with Graphene toward High‐Sensitivity and Fast‐Response Bulk‐Silicon Schottky Photodetector

Abstract: Silicon‐based electronic devices, especially graphene/Si photodetectors (Gr/Si PDs), have triggered tremendous attention due to their simple structure and flexible integration of the Schottky junction. However, due to the relatively poor light–matter interaction and mobility of silicon, these Gr/Si PDs typically suffer an inevitable compromise between photoresponsivity and response speed. Herein, a novel strategy for coupling 2D In2S3 with Gr/Si PDs is demonstrated. The introduction of the double‐heterojunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…vdW heterostructures to construct Schottky barrier junction photodiodes. [9][10][11][12][13] In this type of photodiodes, the bulk semiconductors absorb photons to generate electron-hole pairs, and the 2DMs act as transparent Schottky electrodes to collect the photoinduced carriers. The photoexcited electron-hole pairs are immediately and efficiently separated by the built-in electric field at the adjacent interface between 2DMs and the underlying semiconductors, resulting in photocurrent as a function of incident light power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vdW heterostructures to construct Schottky barrier junction photodiodes. [9][10][11][12][13] In this type of photodiodes, the bulk semiconductors absorb photons to generate electron-hole pairs, and the 2DMs act as transparent Schottky electrodes to collect the photoinduced carriers. The photoexcited electron-hole pairs are immediately and efficiently separated by the built-in electric field at the adjacent interface between 2DMs and the underlying semiconductors, resulting in photocurrent as a function of incident light power.…”
Section: Introductionmentioning
confidence: 99%
“…The photoexcited electron-hole pairs are immediately and efficiently separated by the built-in electric field at the adjacent interface between 2DMs and the underlying semiconductors, resulting in photocurrent as a function of incident light power. [10] It has been reported that the graphene/Si photodiode with ultra-shallow junction possesses internal quantum efficiency approaching the upper-limit of Si based ultraviolet PDs. [14] Nevertheless, the complex transfer process for the fabrication of vdW heterojunction PDs hinders their applications for large-scale, high-integration devices.…”
Section: Introductionmentioning
confidence: 99%
“…As the 2D-Gr and 3D-Gr components have different work functions, the vertical p-n junction interface can be clearly identified in the surface potential images. The difference between the Fermi levels in the 2D-Gr and 3D-Gr layers, ΔE f , can be expressed via the following equations [30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…Scanning Kelvin probe microscopy (SKPM) is an effec tive method to explore the flow of the separated electrons and holes by measuring the surface potential difference (SPD) between graphene and Ge nanodots without and with light irradiation. [33][34][35][36] SPD is defined by the difference in the Fermi level between graphene and Ge nanodots as shown in the following: E e P eP e P f g raphene G e G e g raphene…”
Section: Resultsmentioning
confidence: 99%